2020
DOI: 10.3389/fimmu.2020.00682
|View full text |Cite|
|
Sign up to set email alerts
|

Recirculation and Residency of T Cells and Tregs: Lessons Learnt in Anacapri

Abstract: Location, location, and location": according to this mantra, the place where living beings settle has a key impact on the success of their activities; in turn, the living beings can, in many ways, modify their environment. This idea has now become more and more true for T cells. The ability of T cells to recirculate throughout blood or lymph, or to stably reside in certain tissues, turned out to determine immunity to pathogens, and tumors. If location matters also for human beings, the inspiring environment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 74 publications
1
11
0
12
Order By: Relevance
“…It has been reported that skin-resident T-cells do not recirculate; they survive and proliferate in the skin without migrating to the lymph nodes 63 , 64 . More recent studies have shown that human skin CD4 + resident memory T cells can exit the skin, reenter the circulation, and travel to secondary human skin sites 65 , 66 , supporting our model of the spreading of CTCL lesions. Previous studies with TCR-sequencing also supported this model by demonstrating low but detectable malignant clones in adjacent non-lesional skin and peripheral blood in patients with skin-limited CTCL 67 , 68 .…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that skin-resident T-cells do not recirculate; they survive and proliferate in the skin without migrating to the lymph nodes 63 , 64 . More recent studies have shown that human skin CD4 + resident memory T cells can exit the skin, reenter the circulation, and travel to secondary human skin sites 65 , 66 , supporting our model of the spreading of CTCL lesions. Previous studies with TCR-sequencing also supported this model by demonstrating low but detectable malignant clones in adjacent non-lesional skin and peripheral blood in patients with skin-limited CTCL 67 , 68 .…”
Section: Discussionsupporting
confidence: 82%
“…Since CD69+CD103+ T cells were observed at 15 weeks post- LmCen -/- immunization at which point we could not recover any viable parasites, it is unlikely that these cells are CD4+ T Reg cells that require the presence of persistent infection ( 36 ). Additionally, the residency of T Reg cells in the non-lymphoid organs in the absence of persistent infection is not fully understood ( 37 , 38 ). Future studies will delineate the roles of T Reg and TRM cells in LmCen -/- vaccine-induced immunity.…”
Section: Discussionmentioning
confidence: 99%
“…4 Aktivacija naivnih T limfocita kao odgovor na antigen i njihova kasnija proliferacija i diferencijacija predstavlja primarni imunološki odgovor. [7][8][9] Istovremeno s obezbjeđivanjem efektorskih T ćelija, primarni imunološki odgovor stvara imunološku memoriju, koja pruža zaštitu od naknadnog izlaganja istog patogena. 1…”
Section: Naivni T Limfocitiunclassified
“…Peripheral Lymphoid Organs, PNO) u cilju aktivacije antigenima i transformacije u efektorske ćelije. 9 Kretanje limfocita predstavlja uređen slijed koji počinje regrutovanjem cirkulišućih limfocita na luminalnoj površini krvnog suda (uključujući interakciju limfocita sa endotelom, njihovo kotrljanje i na kraju čvrstu adheziju za unutrašnjost krvnog suda). 10,11 Slijedi intravaskularna migracija luminalno adheriranih limfocita (translokaciju sa početnog mesta vezivanja na odgovarajuće izlazno mjesto), transendotelna tranzicija, te migracija unutar ekstravaskularnog kompartmenta u parenhimu.…”
Section: Recirkulacija Naivnih T Limfocita U Perifernim Limfoidnim Or...unclassified
See 1 more Smart Citation